2015
DOI: 10.3109/13880209.2015.1042980
|View full text |Cite
|
Sign up to set email alerts
|

Olive oil and its phenolic compounds (hydroxytyrosol and tyrosol) ameliorated TCDD-induced heptotoxicity in rats via inhibition of oxidative stress and apoptosis

Abstract: Context: Naturally occurring polyphenols including olive oil (OO) and its constituents hydroxytyrosol (HT) and tyrosol (TY), consumed in the Mediterranean diet, have shown to treat various ailments due to their remarkable antioxidant properties. Objective: The present study investigates the hepatoprotective effects of OO and its phenolic compounds HT and TY against TCDD-induced hepatotoxicity in male Wistar rats. Materials and methods: TCDD was administered at a dose of 100 ng/kg p.o. for 20 d. Administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…In particular, the polyphenols present in the virgin olive oil display a strong antioxidant activity in vitro [2] and in vivo [3,4], which has impelled a growing interest in these compounds, especially those that can be obtained from by-products of the food industry [5]. Several epidemiological studies have shown the beneficial health effects arising from consumption of foods rich in antioxidants, preventing the damage caused by prolonged oxidative stress in certain biomolecules (nucleic acids, lipids, proteins), which is associated with an increased risk of chronic diseases [6].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the polyphenols present in the virgin olive oil display a strong antioxidant activity in vitro [2] and in vivo [3,4], which has impelled a growing interest in these compounds, especially those that can be obtained from by-products of the food industry [5]. Several epidemiological studies have shown the beneficial health effects arising from consumption of foods rich in antioxidants, preventing the damage caused by prolonged oxidative stress in certain biomolecules (nucleic acids, lipids, proteins), which is associated with an increased risk of chronic diseases [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HT restored the intestinal barrier integrity and functions in mice fed high fat diet [55]. It is also possible that HT can modulate the absorption of lipids in the intestine, especially cholesterol [57], but this effect still requires further investigation. HT-induced enhancement in the antioxidative potential of the liver seems to be associated with activation of nuclear factor-erythroid related factor 2 (Nrf2), a transcription factor controlling the expression of SOD, CAT, GR, and GPX (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, following treatment with the toxin TCDD in male Wistar rats, olive oil, hydroxytyrosol, or tyrosol treatment resulted in an ameliorated TCDD-induced hepatotoxicity. This was linked to inhibition of oxidative stress and apoptosis, with a decrease in Bax protein and an increase in Bcl-2 (Kalaiselvan et al, 2015). As Bax protein favors cell death and Bcl-2 has been shown to inhibit apoptosis (Yang et al, 2002), these results indicate a shift away from pro-apoptotic status.…”
Section: A N U S C R I P Tmentioning
confidence: 91%